Evaluation of Regional Policy on Prohibition of Alcoholic Beverages in Indramayu Regency: A Case Study in Balongan Sub-district, Indramayu - Kartini, Mulyati (Gema Wiralodra, 2025)
This research is to know and understand the performance of local policies on the prohibition of alcoholic beverages in Indramayu Regency, especially in Balongan District. The problem is that the implementation of the policy on the prohibition of alcoholic beverages is still not fully effective. This research uses descriptive research methods with a case study approach. The results of research based on the type of policy evaluation criteria include: Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy show that the six criteria are generally quite good, but still need to be improved in quantity and quality. In addition, there are still obstacles in the field in achieving the effectiveness of policy performance, including social conditions that are not fully supportive, lack of public support from a group of program target communities, less than optimal community participation, lack of support from the central government, especially in evaluating local regulations that have been issued by local governments. The limitation of this research is that it was only conducted in Balongan District, Indramayu Regency. In the future, it is necessary to conduct research with the locus of all sub-districts in Indramayu Regency in order to know the effectiveness of policy performance, constraining factors and policy recommendations, so as to achieve more effective policy goals and objectives.